Identidad y turismo en los paisajes de la sal = Identity and tourism in the landscapes of salt - Fariña Tojo, José (Cuadernos de Investigación Urbanística, 2020)
RESUMEN:Se analiza la relación entre elementos identitarios relacionados con el paisaje de las salinas y los efectos sobre el mismo que tiene su consideración como producto turístico. También los efectos de las nuevas tecnologías de la información y la comunicación en la formación de la imagen y la correspondiente metáfora dellugar.ABSTRACT:Is analysed the relationship between identity elements related to the landscape of the salt flats and the effects on it that has its consideration as a tourist product. Also, the effects of the new information and  communication technologies in the formation of the image and the corresponding metaphor of theplace.